FAKTOR YANG BERHUBUNGAN DENGAN KEIKUTSERTAAN PASANGAN USIA SUBUR DALAM PROGRAM KELUARGA BERENCANA DI KELURAHAN SEMELAGI KECIL - Gabriela Advitri Febriani; Yesi Vila Delpia; Adhetya Uberty; Dilly Ekasari; Silfia Sekar Arum M.E Susanti (Poltekkes Kemenkes Maluku, 2026)
Background: Family Planning Program is one of the government’s efforts to improve public health quality, particularly in reducing maternal mortality and infant mortality rates. Through family planning programs, reproductive-age couples are able to plan the number and spacing of children, thereby creating healthy and prosperous families. Objective: This study aimed to determine the factors associated with participation of reproductive-age couples in the Family Planning Program. Methods: This study employed an analytical observational design with a case-control approach. The population consisted of reproductive-age couples in Semelagi Kecil Village of UPT Puskesmas Singkawang Utara I. The case sampling technique used total sampling with a total of 118 reproductive-age couples who did not participate in the family planning program, while the control sample used simple random sampling with a total of 118 reproductive-age couples who participated in the family planning program. Data were analyzed using the Chi-square test. Results: The results showed a significant relationship between maternal age and participation in the Family Planning Program (p-value = 0.027). There was also a significant relationship between parity and participation in the Family Planning Program (p-value < 0.001), as well as between maternal occupation and participation in the program (p-value = 0.032). Meanwhile, there was no significant relationship between maternal education level and participation in the Family Planning Program (p-value = 0.182), nor between family income and participation in the program (p-value = 0.362). Conclusion: Maternal age, parity, and occupation are related to participation in family planning, while education and income are not related to participation in family planning